Executive function in the school context: The role of peer relationships. Issue 1 (16th August 2019) - Lecce, Serena; Bianco, Federica; Ronchi, Luca
Abstract: Theoretical accounts and experimental data on young children have shown that executive functions (EFs) are predicted by experiential factors. However, studies on school‐aged children are rare. The present study has addressed this gap using a short‐term cross‐lagged longitudinal design focusing on the relationship between working memory (WM), conflict inhibition (CI), and peer acceptance (PA) and rejection (PR) in middle childhood. 245 children, aged 8 to 12 years at Time 1 ( M = 10.03 years, SD = 1.21 years), were tested three times over 1 year. SEM showed that (a) PA at Times 1 and 2 positively predicted WM at Times 2 and 3 and (b) PR at Time 1 negatively predicted CI at Time 2. Our findings are in line with the view that EFs are significantly affected by children's social life at school and are interpreted in light of the regulatory depletion model and of the socio‐constructivist models. Highlights: We examine cross‐lagged associations between children's peer relationships and executive functions in the school context. Peer acceptance predicts working memory development and peer rejection predicts inhibition development in middle childhood. Executive functioning development is sensitive to children's social experiences with peers at school.